(3LdGA GdCfXGQ aj Md YhjUGJ GdCacGQs - (3bQI Ndjd, Ndjd Hf MSf GdJjQGhj, J (B1123s
(3ChdgG (B:s
(3MeOG dc Gddge Ydi eG CaVdJ dj ef BdGA GdCaGVd hTcQG dc Ydi eG fYeJ dj ef fYeGA GdCeGKd hUdGI hSdGeG Ydi eMeO GdgGOj CeJg HChVM GdOdGFds
(3BNQgG (B:s
(3aEf Gdaf ef COb GdYdhe MJi UQM TGQM GdeWGdY aj ehGVY ef cJGHg GdeaUd ZGjI GdJaUjd HCfg eNJUQ hGYJPQ aj cKjQ ef GdeSGFd dG jdjb JaUjdg gPG GdeNJUQs
(3LGA aj fgGjI GdeNWhW Cf GdeDda GfJgi ef SWQ MGTjJg jhe GdLeYI SfI CQHY YTQI heGFI hCdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/317s
(3eYLe GdeDdajf (B1 / 683s
(3gOjI GdYGQajf (B1 / 354s
(3YKeGfdj eDdadQj (B1 / 403s
Keywords: (3GdadSaI hGdefWbs